Pengaruh varietas dan dosis kompos yang diperkaya Trichoderma harzianum terhadap pertumbuhan dan hasi tanaman cabai merah (Capsicum annuum L.) - Sepwanti, Christina; Rahmawati, Marai; Kesumawati, Elly (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala)
A field experiment to evaluate the effect of variety and Trichoderma harzianum compostÂ doses which riches on the growth and yield of red chilli was carried out at the Experimental Farm Agricultural Faculty Syiah Kuala University, from May 2013 through to January 2014. The experiment was arranged in a Randomized Block Factorial Design with two replications. The treatment one consisted of three variety i.e.: F-1 Paramas 201, Ferosa var CA. 237 and Kheng Aik, the treatment two consisted of four doses T. harzianum compost i.e.: control, 10 g per plant, 20 per plant and 30 g per plant. The result showed that the variety and T. harzianum compostÂ doses increased growth and yield of red chilli, and the variety F-1 Paramas 201 was found to give the highest plant, long fruit, height per fruit, fruit number per plant and fruit weight per plant and dosage of 20 g per plant of T. harzianum compost was found to give the fruit number per plant, height per fruit and fruit weight per plant.